(untitled) (Fiep Bulletin - online, 2011)
At least 60% of world population can not complete the recommended amount of physical activity programs and only show common and with limited results. Objective: To evaluate and compare the clinical and teaching a program of physical activity and lifestyle variables in adaptive behavior, knowledge, body composition and physical fitness and health and levels of physical activity in people with intellectual disabilities, their families community and coming from a school of Special Education, Ceilandia-DF, and its surroundings. Methods: The sample consisted of 400 persons of both sexes aged 6 e75 years divided into four groups (students, managers, education professionals and community). This is a longitudinal study on the effect of a program to promote physical activity and social inclusion, conducted over two years, assessed by questionnaire, physical tests and tests of body composition. Results: There was a 20% improvement in overall knowledge about disabilities, differences between ages in the abdominal and aerobic endurance (.05 and .04) and a slight improvement in the group 15> but not significant Conclusion: Both groups had significant variance, demonstrating low levels of physical activity, negative life style among them but not most of the data pre and post test were not significant which means that more studies and school-based interventions should be conducted.